PEMEROLEHAN BAHASA ANAK USIA 2–3 TAHUN DITINJAU DARI ASPEK FONOLOGI - Erna Haryanti; Ari Dwi Lestari; Teti Sobari (IKIP Siliwangi, 2018)
Language is an important means for people to communicate. Language as a means of communication is derived from the birthplace that is called the acquisition of language. Language acquisition in children begins with their learning to speak. This study aims to expose the acquisition of children's language ages 2 to 3 years in terms of phonological aspects including vocal domination, consonants, and factors affecting the acquisition of the child's own language. In addition, this research can help parents to supervise the development of children's language, anticipate the confusion of spoken language with the true meaning, and to know how to overcome the language barrier in the child when there is a disturbance to the children's speech tools. Method used in this research is qualitative method. With this method the result of the research is described according to the purpose, so the data obtained is easier to be informed